Wood inspection using digital radiography / Muhammad Haffizal Musa - Musa, Muhammad Haffizal (2010)
The non-destructive testing nowadays has become more advanced in order to follow the development of technology and new trend. For example in radiography, one technique called digital radiography that uses the advanced computer technology, scanner machine and data editor established. Meanwhile, research was made based on the digital radiography technology. This research is based on wood inspection using digital radiography to obtain the high quality image of radiography. The inspection was made because there was no other inspection regard to the wood. The purpose of this inspection is to determine the relationship of penetration power and source-to-film distance with the image quality. Besides, the purpose is to evaluate the wood thickness with the image quality. In addition, the inspection done to establish basic exposure chart that include parameter such as penetration power, exposure time, current and wood thickness. These parameter affect the quality of image displayed on the monitor. There are three type of wood used; Akasia, Perah, and Meranti. The three different type of wood divided into three thickness; 2 inches (50.2mm), 3 inches (76.2mm) and 5 inches (127mm).